Pleural Amebiasis without Hepar Involvement - Handayani, Friska; Medison, Irvan; Fitrina, Dewi Wahyu; Mizarti, Dessy (Universitas Muhammadiyah Semarang, 2023)
Background: Pleuropulmonary amebiasis is the most common complication of amoebic liver abscess, occurring in 15% of patients with amoebic liver disease and in 1% of patients with amoebic dysentery. Most commonly occurs by direct extension of a right superior lobe hepatic abscess through the diaphragm to the right lower lobe of the lung with a mortality rate of 5-16%. Primary pleural amebiasis without liver involvement is rare.Case Presentation: Reported an 18-year-old male patient with pleural amebiasis from the results of parasitological examination of pleural fluid found Entamoeba histolytica. History, physical examination and support showed normal liver function. The patient has a history of poor sanitation with a dissertation of unhygienic habits. Patients without liver problems remain at risk for amoebiasis pleuraConclusion: Pleural amebiasis without liver involvement was a rare case. Further investigation was needed in patients with pleural amoebiasis to other organs, such as the liver and digestive tract. Diagnose pleural amebiasis should be the main focus in determining the etiology. Entamoeba histolytica may be involved in pleural inflammation and cause effusion.